2018
DOI: 10.1007/s00345-018-2322-7
|View full text |Cite
|
Sign up to set email alerts
|

Oligorecurrent prostate cancer limited to lymph nodes: getting our ducks in a row

Abstract: Newer PET/CT radio-labeled tracers have increased disease detection in oligorecurrent prostate cancer patients. Growing evidence of their impact on metastasis-directed therapy encourages the use of the most advanced radiotherapy techniques in the clinical management of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In fact, in these subjects the risk of misdiagnosing disseminated micrometastatic disease as oligorecurrent PCa would be minimized. [ 56 ] However, an argument against this hypothesis is that these patients could be the ones with latent metastatic PCa, which was simply not detected in the past due to less sensitive tracer (given the low metabolic uptake of these lesions) and which have a very good prognosis even without any intervention. Furthermore, it could be hypothesized that even selected tumors with short PSA doubling time could be managed with MDT, given the possibility of repeating the latter until widespread metastatic diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in these subjects the risk of misdiagnosing disseminated micrometastatic disease as oligorecurrent PCa would be minimized. [ 56 ] However, an argument against this hypothesis is that these patients could be the ones with latent metastatic PCa, which was simply not detected in the past due to less sensitive tracer (given the low metabolic uptake of these lesions) and which have a very good prognosis even without any intervention. Furthermore, it could be hypothesized that even selected tumors with short PSA doubling time could be managed with MDT, given the possibility of repeating the latter until widespread metastatic diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies reported a positive impact of ADT use concomitant to RT [5] , while others showed no benefit [34] , [35] . Another trials investigated RT alone with the aim to defer the onset of ADT [36] . For example, Fodor et al demonstrated that patients with nodal oligorecurrence had 25 to 44 months ADT-free survival time after SBRT of lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it is very important to update health providers about the recent advances in technology, which have changed dramatically the clinical scenarios in oncology, allowing dose escalation in radiotherapy, decreasing toxicity and treatment duration with improved oncologic outcome and with less impact on patients’ quality of life. Techniques such as intensity-modulated radiation therapy (IMRT)22 or stereotactic radiotherapy5,7,23 create highly conformal dose distributions with steep dose gradients using advanced planning and treatment equipment. Eventually, image-guided radiotherapy (IGRT) permits daily target localization to guide the dose delivery 24.…”
Section: Physician Barriersmentioning
confidence: 99%